Morphology of heal and jejunal pouches used as rectal substitutes - Teixeira, F. V.; Daud, D.; Eleuterio, M. L.; Silva, MDP; Kelly, K. A. (Lippincott Williams & Wilkins, 2003)
PURPOSE: Our aim was to determine whether the mucosa of a canine jejunal pouch used as a rectal substitute after proctocolectomy retains its morphologic features better than the mucosa of a canine ileal pouch so used. METHODS: Among ten dogs that underwent proctocolectomy, five had a jejunal pouch-distal rectal anastomosis and five an ileal pouch-distal rectal anastomosis. After six months, the animals were killed, the intestinal pouches and portions of unaltered distal ileum were removed, and a blinded, mucosal morphometric analysis was performed. RESULTS: the mucosa of the jejunal pouches had an overall thickness (mean standard deviation, anterior and posterior walls, 1,300 140 Am), villous height (286 +/- 46 mum), and crypt depth (790 77 Am) greater than that of the ileal pouches (920 +/- 170, 208 +/- 47, and 530 +/- 130 mum, respectively; P < 0.05). Moreover, the mucosal thickness of the jejunal pouches was similar to that of the distal ileum proximal to the pouch (1,200 +/- 200 mum; P > 0.05), whereas the mucosal thickness of the ileal pouch was thinner (P < 0.05). CONCLUSIONS: the jejunal mucosa retains its major morphometric features when the jejunum is used as a rectal substitute after proctocolectomy. In contrast, the ileal mucosa atrophies when the ileum is so used.
Keywords: proctocolectomy; ileal pouch-anal canal anastomosis; jejunal pouch-anal canal anastomosis